(untitled) (Research, Society and Development, 2021)
Suicide is a phenomenon of multifactorial causes, in which the individual tries against his own life. For sociologist Durkheim, this is considered a social fact, since society contributes to suicide to occur. It is the 3rd leading cause of death in the world and Brazil is among the 10 countries with the highest cases. More than 800 thousand people commit suicide every year, representing one death every 40 seconds, in Brazil it is every 46 minutes. The most affected are men, white, single and of low income. The age group with the highest incidence is 15 to 29 years. There are preponderant factors for this to occur, such as: mental illnesses, social and psychological aspects and the individual’s health conditions, highlighting the major cause of suicide, with 35.8%, mental disorders. The Brazilian region with the highest rates is the Southeast, followed by the South, Northeast, Midwest and North regions. Through this, a systematic review of the literature of the last 9 years (2013-2021) was carried out in the databases: SciELO, Pubmed, MedLine, Scienc Direct and Lilacs, in English, Portuguese and Spanish, crossing the keywords suicide, causes, Brazil and epidemiological profile. Therefore, further studies on the topic in question are necessary, as well as an improvement in primary care and the performance of mental health care and the family health strategy for better suicide prevention.